Recursos didácticos en la asignatura de cultura física, énfasis en vóley, fútbol y en básquet; y su incidencia en la profesionalización de la carrera de educación básica de la universidad técnica de cotopaxi, extensión la maná, año 2014-2015 - Niola Pelaez, Diana Elizabeth (2015)
This research raised designing an internship program of pre-sports games of volleyball, soccer and basketball that affect students professionalizing of the Bachelor in Basic Education, for which several methods were applied to classes Culture Physics as: duration, interval, repeat, alternate control method and circuit training in order to better develop the teaching, the same as were long intervals, repetition, alternation, control and training methods circuit; also for programming the motor tasks was taken into consideration features such activity, variety, meaning, direction, inquiry, inclusiveness and openness.